Effect of combining lower- and higher-value monthly cash transfers with nutrition-sensitive agriculture, male engagement, and psychosocial intervention on maternal depressive symptoms in rural Malawi: A secondary analysis of a cluster-randomised controlled trial - Bliznashka, Lilia; Nwabuikwu, Odiche; Ahun, Marilyn; Roschnik, Natalie; Phiri, Brenda; Gondwe-Matekesa, Esnatt; Kachinjika, Monice; Mvula, Peter; Munthali, Alister; Maggio, Daniel; Katundu, Mangani; Maleta, Kenneth; et al. (MedRxiv, 2024)
Maternal depression affects one in five women in Malawi. Integrated interventions simultaneously addressing multiple risks are a promising strategy to improve mental health. This study evaluated the impact of a nutrition-sensitive social behaviour change (SBC) interventions (agriculture and livelihoods, male engagement, and Caring for the Caregiver) with or without cash transfers on maternal perinatal depression during the lean season in rural Malawi. A midline survey for a cluster-randomised controlled trial was conducted, where 156 clusters were randomly assigned to four arms (39 clusters/arm): (1) Standard of care (SoC), (2) SBC, (3) SBC+low cash (USD17 per month), and (4) SBC+high cash (USD43 per month). Pregnant women and mothers of children <2 years of age (n=2,682) were enrolled at baseline (May-June 2022). A subsample of 1,303 women were followed-up at midline (November-December 2023). Maternal perinatal depression was assessed using the Self-reporting Questionnaire (SRQ-20) with a score of ≥8 indicating symptoms consistent with depression. Intervention effects were estimated using linear mixed effects models. At midline, SBC+high cash reduced depression scores relative to SoC (mean difference (MD) -1.13 (95% CI -1.96, -0.31)) but had no impact on the proportion of women with depressive symptoms. SBC+low cash and SBC alone had no impact on depression scores or the proportion of women with depressive symptoms. Relative to SBC alone, adding cash to SBC reduced depressions scores and the proportion of women with depressive symptoms regardless of the size of the cash transfer. Cash transfers integrated with SBC can benefit maternal perinatal depression health in rural Malawi during the lean season.